Efektifitas Teknik Komunikasi Daring Sinkron, Asinkron dan Motivasi Kerja, dalam Sosialisasi Implementasi Kurikulum Merdeka (IKM) Terhadap Pemahaman Pendidik Tentang Kurikulum Merdeka di SMP Negeri Babelan Kabupaten Bekasi - Rahmat Surya Sutrisna; Siti Masitoh (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose of this study was to analyze the effect of communication effectiveness and work motivation on teachers' understanding of the independent curriculum and the effect of communication effectiveness and work motivation on teachers' knowledge of the independent curriculum. This type of research is a survey in the form of a questionnaire for educators at SMPN Babelan. The target population is SMPN Babelan educators, as many as 206 people, a sample of 136 educators based on the Slovin formula with random sampling. They are collecting data using a questionnaire with a Likert scale. Data analysis used validity and reliability tests, normality tests, classical assumption tests (data normality, multicollinearity, heteroscedasticity, autocorrelation), multiple linear regression tests, hypothesis tests (t-test, F-test), and determination tests. The results showed that the classical test showed the data were normally distributed Sig. = 0.800 > 0.05, there were no symptoms of multicollinearity, heteroscedasticity occurred, and there was no autocorrelation (dw value lies between 2 and (4-du)) in the regression model used. Communication effectiveness is the variable that influences teachers' understanding of the independent curriculum because the regression coefficient value is 0.464, more significant than work motivation (0.374). The value of F = 42.056 is obtained, and the importance of Sig. = 0.000 <0.05 means that hypothesis H0 is rejected, and hypothesis Ha is accepted because the significance probability value is 0.000 <0.05. Communication effectiveness and work motivation affect teachers' understanding of the independent curriculum by 38.7%. The remaining 61.3% is influenced by other variables not included in this research model. In conclusion, there is a positive and significant influence between communication and work motivation on teachers' understanding of the independent curriculum. Keywords: Communication Effectiveness, Independent Curriculum, Work Motivation,